Suelos y vulcanismo: Argentina. Perla Imbellone & Osvaldo Andrés Barbosa (Editores) 1a ed.- Ciudad Autónoma de Buenos Aires: Asociación Argentina de la Ciencia del Suelo -AACS, 2020. Libro digital, PDF - ISBN 978-987-46870-2-9 - Luis Spalletti (Revista del Museo de La Plata, 2020)
..